Immigration building / Mohamad Aziz Izzuddin Baharom... [et al.] - Baharom, Mohamad Aziz Izzuddin; Tajuddin, Shafiq Taqiuddin; Sahdun, Mohammad Hasif Hazim; Joseph Garan, Benedict Sandin; Shamshul Bhari, Siti Nurbaya (2015)
Large building is a complex thing to be manage. It must be manage in proper way to prolong the building life and increase the value of the building by avoiding any problem occur that can harm the building and the occupants of the building. To manage a large building, someone must have knowledge on all aspect such as in management aspect and maintenance aspect to handle the property efficiently. Purpose of this investigation on Immigration building that located at Putrajaya is to reveal the important aspects of maintenance management, technology, design, property, building economic, finance, law, communications, project planning and project management of the building. Immigration building is a large building category and to control the building is not a easy work. There are many systems to be control and maintain to operate the building. Without proper method of controlling and maintenance the building will not able to operate smoothly. In this report there are information about how the building is operated. There are include all types of system been used by Immigration building to be operate efficiently. It also provide all aspects that must be taken to operate the building. In conclusion, a large building is a very complex to be manage. It need a proper management and maintenance to operate the building. Aspects such as maintenance management, technology, design, property, building economic, finance, law, communications, project planning, and project management of the building is a important aspects to operate the building smoothly.